2007
DOI: 10.1097/opx.0b013e3180dc99be
|View full text |Cite
|
Sign up to set email alerts
|

Eyelid Squint Response to Asthenopia-Inducing Conditions

Abstract: Refractive error and glare, which reduce image quality and benefit from eyelid squint, caused increased EMG power, eyelid squint response and increased blink rate. Low contrast and small font, which reduce image quality but do not benefit from eyelid squint, resulted in increased EMG power without changes in aperture size and reduced blink rate (for low contrast). Accommodative and convergence stress (in subjects with normal accommodative and vergence abilities) did not cause changes in EMG power, aperture siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 17 publications
2
26
0
Order By: Relevance
“…It has also been shown that low contrast and small font resulted in eyelid squint and reduced blink rate 27. Other studies have reported a reduction in blink rate as the level of required concentration and cognitive demands increased when performing different visual tasks 18,28.…”
Section: Discussionmentioning
confidence: 96%
“…It has also been shown that low contrast and small font resulted in eyelid squint and reduced blink rate 27. Other studies have reported a reduction in blink rate as the level of required concentration and cognitive demands increased when performing different visual tasks 18,28.…”
Section: Discussionmentioning
confidence: 96%
“…These authors hypothesized that the change in inter‐blink duration during the course of VDT operation represented cognitive adaptation to the computer task. Further, no significant correlation was observed between clinical measurements of the ocular tear film (tear breakup time, Schirmer I or Jones tests) and the observed blink rate during computer operation.It has also been reported that blink rate decreases as font size and contrast are reduced, 70 or the cognitive demand of the task increases 71,72 . Additionally, Sheedy et al.…”
Section: Cvs and Dry Eyementioning
confidence: 95%
“…It has also been reported that blink rate decreases as font size and contrast are reduced, 70 or the cognitive demand of the task increases 71,72 . Additionally, Sheedy et al.…”
Section: Cvs and Dry Eyementioning
confidence: 95%
“…However, these 3 testing conditions varied not only in the method of presentation, but also in task format. It has been noted that blink rate decreases as font size and contrast are reduced (Gowrisankaran, Sheedy, & Hayes, 2007), or the cognitive demand of the task increases (Cardona, Garć ia, Serés, Vilaseca, & Gispets, 2011;Himebaugh, Begley, Bradley, & Wilkinson, 2009;Jansen, Begley, Himebaugh, & Port, 2010 observed by Tsubota and Nakamori may be related to changes in task difficulty, rather than being a consequence of changing from printed material to an electronic display. Indeed, a recent study in our laboratory compared blink rates when reading identical text from a desktop computer screen versus hardcopy printed materials (Chu, Rosenfield, & Portello, 2014).…”
Section: Introductionmentioning
confidence: 99%